A Case of Radial Nerve Palsy - Mun Kyung-suk; Lee Kwang-ho; Kim Tae-woo; Jang Bo-Hyoung; Kweon O-seop; Ryu Chung-ryeul; Cho Myung-rae (Journal of Pharmacopuncture, 2004)
Objective : The purpose of this study is to report the patient with radial nerve palsy, who improved by oriental medical treatment. Methods : The patient was managed by Cathami Flos aqua-acupuncture, Dong-Qi acupuncture treatment, Comman acupuncture treatment and Herbal medicine. We took pictures of patient's wrist and checked the power of muscles. And we checked the numbness of thumb that was patient's subjective sensation. Results : After 2 weeks-treatment, the movement and power of wrist was restored to nearly normal range, also the numbness of thumb was removed. Combined oriental medical treatment can treat radial nerve palsy earlier than the other methods. Conclusions : The results suggest that combination of Cathami Flos aqua-acupuncture, Dong-Qi acupuncture treatment, Comman acupuncture treatment and Herbal medicine is good method for treatments of radial nerve palsy. But further studies are required to concretely prove the effectiveness of this method for treating radial nerve palsy.